2022
DOI: 10.1111/iju.15112
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of robot‐assisted partial nephrectomy with soft coagulation and double‐layer technique for complex and non‐complex tumors

Abstract: Abbreviations & Acronyms BMI = body mass index CT = computed tomography DLT = double-layer technique eGFR = estimated glomerular filtration rate LPN = laparoscopic partial nephrectomy MDRD = Modification of Diet in Renal Disease RAPN = robot-assisted partial nephrectomy SLT = single-layer technique WIT = warm ischemia time

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In terms of the renorrhaphy method, no significant differences were noted in LOS, renal function, or incidence of postoperative complications, although SILR contributed to a reduction in operative time and WIT [26]. The operative time, console time, WIT, and LOS did not significantly differ according to the renorrhaphy method used; however, the incidence of urinary leakage or urinoma was significantly higher in the SILR group compared with in the DLR group [27]. One of the primary concerns related to SILR is the occurrence of postoperative complications, especially bleeding and urinary leakage [28].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In terms of the renorrhaphy method, no significant differences were noted in LOS, renal function, or incidence of postoperative complications, although SILR contributed to a reduction in operative time and WIT [26]. The operative time, console time, WIT, and LOS did not significantly differ according to the renorrhaphy method used; however, the incidence of urinary leakage or urinoma was significantly higher in the SILR group compared with in the DLR group [27]. One of the primary concerns related to SILR is the occurrence of postoperative complications, especially bleeding and urinary leakage [28].…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, multivariate analysis revealed that renorrhaphy was an independent predictor of renal volume loss after RAPN (p < 0.01) [10]. Another study demonstrated that patients who underwent SILR reported a shorter WIT and lower rate of worsening eGFR and renal volume at 4 months postoperatively compared with those who underwent DLR [27]. Renorrhaphy and the resulting traumatic lesions may be more crucial than the amount of tumor resected in predicting residual renal function after RAPN [6].…”
Section: Discussionmentioning
confidence: 99%
“…Kishore et al reported that single-layer cortical renorrhaphy is associated with a reduced rate of renal artery pseudoaneurysm compared to double-layer renorrhaphy 3 . In contrast, Shiozaki et al revealed that singlelayer suturing with soft coagulation achieved renal function and perioperative outcomes comparable to those of double-layer suturing regardless of tumor complexity 4 . Although these studies adjusted for patients or tumor backgrounds to compare surgical outcomes according to the reconstruction techniques, the surgeon's skill might not have been collectively adjusted because several surgeries were included in their studies.…”
Section: Introductionmentioning
confidence: 97%
“…Several techniques have been proposed to reconstruct the tumor bed after tumor resection, such as single-layer renorrhaphy, double-layer renorrhaphy, and sutureless coagulation of the bed. The optimal reconstruction methods have been discussed in terms of e cacy and feasibility [3][4][5][6] . Kishore et al reported that single-layer cortical renorrhaphy is associated with a reduced rate of renal artery pseudoaneurysm compared to double-layer renorrhaphy 3 .…”
Section: Introductionmentioning
confidence: 99%